EFFECTIVE STRATEGIES IN UNDERSTANDING ARABIC GRAMMAR - Rayhanur Royyan; Nasiruddin (Al-Masail: Journal of Islamic Studies, 2024)
This research was motivated by students' difficulties and errors in learning grammar. One of the reasons for this is that the learning methods or approaches applied are not optimal. This research aims to provide an overview of grammar learning strategies or approaches so that they can be implemented optimally. This research uses a qualitative approach, with the type of research being a literature study. Data sources come from books or scientific works that are relevant to the research theme. Data was collected by looking for weighty information related to the research theme. Data analysis starts from data reduction, data presentation, then drawing conclusions. The results of this research show that there is an important approach to apply in grammar learning, namely the gradual approach. What this means is that learning grammar starts from the basic level, moves on to the intermediate level, then advanced level.